Corruption: Engineers are Victims, Perpetrators or Both? - Pecujlija, M.; Cosic, I.; Nesic-Grubic, L.; Drobnjak, S. (Science & Engineering Ethics, 2015)
This study was conducted in Serbian companies on licensed engineers and in its first part included a total of 336 licensed engineers who voluntarily completed the questionnaires about their ethical orientation and attitudes toward corruption and in the second part 214 engineers who participated in the first survey, who voluntarily evaluated their company's business operations characteristics. This study has clearly shown that there is a direct significant influence of the engineer's ethical orientations and attitudes toward corruption on their evaluation of the characteristics of their respective companies regarding business operations. This research also clearly shows that only engineers with a strong deontological orientation, low ethical subjectivity, and strong readiness to fight corruption, low corruption acceptance and high awareness of corruption can successfully fight corruption, improve the business operations of their companies and make beneficial changes to society. Otherwise, they should be considered as corruption perpetrators, not just as its victims.